Clinical and Molecular Profile of Infantile-Onset Pharmaco-Resistant Epilepsy in Iraqi Children - Saadi, Nebal Waill; Makhseed, Nawal; Al-Husseinawi, Ali Kadhim; Marafi, Dana (International Journal of Epilepsy, 2025)
Identifying the underlying genetic etiology of epilepsy and neurodevelopmental disorders can greatly inform clinical management from diagnosis to treatment to genetic counseling about prognosis. The aim of the study was to establish the genetic/molecular diagnosis in children presenting to two children hospitals in Baghdad, with infantile-onset epilepsy.Twenty-nine Iraqi children with infantile-onset epilepsy, defined as epilepsy with onset in the first year of life, presenting between April 2018 and June 2021, were included in this prospective study.An overall molecular diagnostic rate of 65.5% (in 19/29 subjects) was achieved. Of the subjects with molecular diagnosis, 74% (14/19 subjects) were diagnosed by clinical exome sequencing and 26% (5/19 subjects) were diagnosed by the epileptic encephalopathy panel. Single nucleotide variants were detected in 95% (18/19 subjects) while copy number variants accounted for 5% of the cohort (1/19 subjects). Thirteen subjects (68%) had known pathogenic or likely pathogenic variants in the following genes: SCN1B, SCN1A, ALG13, STXBP1, TBC1D24, PRUNE1, ALDH7A1, PCDH19, SCN8A, and SLC13A5. Six patients (32%) had novel variants potentially explaining the phenotype in the following known genes: SYNJ1, SLC25A22, SCN2A, KCNT1, CACNA1A, and PLPBP. Half (9/19; 47%) of the molecularly diagnosed cases had therapeutic implications.This is the first study to characterize the genotypic and phenotypic spectrum of infantile-onset drug-resistant epilepsy in children from Iraq. Our study demonstrates a high molecular yield with genetic heterogeneity and predominance of autosomal recessive mode of inheritance.
Keywords: infantile; epilepsy; pharmaco-resistant